Tobacco use amongst out of school adolescents in a Local Government Area in Nigeria - Sangowawa Adesola O; Faseru Babalola; Adebiyi Akindele O; Owoaje Eme T (BMC, 2010)
Abstract Introduction Out-of-school adolescents are often neglected when planning for tobacco prevention programmes whereas they are more vulnerable. Few studies exist in Nigeria about their pattern of tobacco use to serve as the basis for effective policy formulation. Method A sub sample of 215 out of school adolescents was analyzed from a descriptive cross sectional study on psychoactive substance use amongst youths in two communities in a Local Government Area in Nigeria which used a multi-stage sampling technique. Results Males were 53% and females 47%. Only 20.5% had ever used tobacco while 11.6% were current users. Males accounted for 60% of current users compared to 40% amongst females. Of current users, 84% believed that tobacco is not harmful to health. In addition, the two important sources of introduction to tobacco use were friends 72% and relatives 20%. Use of tobacco amongst significant others were: friends 27%, fathers 8.0%, relatives 4.2% and mothers 0.5%. The most common sources of supply were motor parks 52% and friends 16%. Conclusion The study showed that peer influence is an important source of introduction to tobacco use while selling of tobacco to adolescents in youth aggregation areas is common. We advocate for a theory based approach to designing an appropriate health education intervention targeted at assisting adolescents in appreciating the harmful nature of tobacco use in this locality. A point-of-sale restriction to prevent adolescent access to tobacco in youth aggregation areas within the context of a comprehensive tobacco control policy is also suggested. However, more research would be needed for an in-depth understanding of the tobacco use vulnerability of this group of adolescents.